(untitled) (Bangladesh Journal of Medical Science, 2016)
Aim: Perforation peritonitis is the most common surgical emergency encountered by surgeons in India. The etiology and sites of perforation shows wide geographical variation. The objective of the study was to find the spectrum of perforation peritonitis & highlight its management at Maharishi Markendeshwar Institute of Medical Sciences & Research, Mullana (MMIMSR). Methods: 93 Operated patients of perforation peritonitis were studied retrospectively in terms of clinical presentation, duration, operative findings and postoperative morbidity and mortality over a period of two years between 2011 to 2013 at MMIMSR Mullana. All the patients had undergone emergency laparatomy under general anesthesia and sites of perforation were identified & managed. Results: The most common cause of perforation peritonititis noticed in our series was peptic ulcer perforation 43 cases (46%), followed by ileal perforation 30 cases (32%), appendicular perforation 6 cases (6.4%), gallbladder perforation 5 cases (5.3%) and all the jejunal perforation 6cases (6.4%) was post traumatic. Large bowel and malignant perforation were least common in our series. Highest no. of perforation noticed in upper part of Gastro intestinal tract as compared to western countries where perforations are seen in distal parts. Mortality was of 11 cases (11.8%) & morbidity was noticed in 55 cases (59%). Conclusion: Peptic ulcer perforation peritonitis is the leading etiology. Mortality is comparable to that of best centre. Aggressive resuscitation and early minimum surgery are required to avoid the high morbidity and mortality. Major complication noticed was wound infection and dehiscence. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.70-73